A simulation study on the dosimetric benefit of real-time motion compensation in spot-scanning proton therapy for prostate. (4th May 2017) - Fujii, Yusuke; Matsuura, Taeko; Takao, Seishin; Matsuzaki, Yuka; Fujii, Takaaki; Miyamoto, Naoki; Umegaki, Kikuo; Nishioka, Kentaro; Shimizu, Shinichi; Shirato, Hiroki
Abstract: For proton spot scanning, use of a real-time-image gating technique incorporating an implanted marker and dual fluoroscopy facilitates mitigation of the dose distribution deterioration caused by interplay effects. This study explored the advantages of using a real-time-image gating technique, with a focus on prostate cancer. Two patient-positioning methods using fiducial markers were compared: (i) patient positioning only before beam delivery, and (ii) patient positioning both before and during beam delivery using a real-time-gating technique. For each scenario, dose distributions were simulated using the CT images of nine prostate cancer patients. Treatment plans were generated using a single-field proton beam with 3-mm and 6-mm lateral margins. During beam delivery, the prostate was assumed to move by 5 mm in four directions that were perpendicular to the beam direction at one of three separate timings (i.e. after the completion of the first, second and third quartiles of the total delivery of spot irradiation). Using a 3-mm margin and second quartile motion timing, the averaged values for ΔD99, ΔD95, ΔD5 and D5–95 were 5.1%, 3.3%, 3.6% and 9.0%, respectively, for Scenario (i) and 2.1%, 1.5%, 0.5% and 4.1%, respectively, for Scenario (ii). The margin expansion from 3 mm to 6 mm reduced the size of ΔD99, ΔD95, ΔD5 and D5–95 only with Scenario (i). These results indicate that patient positioning during beam delivery is an effective way to obtain better target coverage and uniformity while reducing the target margin when the prostate moves during irradiation.